Who is the “WE” that could include immigrants? Different aspects of common ingroups and intergroup competition - Chryssochoou, Xenia; Anagnostou, Ioannis (Psychology: the Journal of the Hellenic Psychological Society, 2019)
The present experimental study, with Greek participants, investigates whether some common ingroups that potentially can include immigrants, in interaction with intergroup competition present more threat for local populations. Results indicate that when the common ingroup is defined as maintaining different memberships (“inhabitants of the country”), redirecting competition towards other outgroups ( other countries) is beneficial to perceptions of migrants. On the contrary, when the common ingroup is presented as blending memberships and presenting commonalities between groups ( “workers”), redirecting competition towards an outgroup ( employers) could be detrimental and produce almost similar results with an intergroup situation where common membership is not salient. These findings have implications both in relation to social psychological theory of Common Ingroup Identity but also in relation to immigrants’ requests for identification and integration.